2017
DOI: 10.3389/fmicb.2017.00311
|View full text |Cite
|
Sign up to set email alerts
|

Whole Genome Sequencing for Surveillance of Antimicrobial Resistance in Actinobacillus pleuropneumoniae

Abstract: The aim of this study was to evaluate the correlation between antimicrobial resistance (AMR) profiles of 96 clinical isolates of Actinobacillus pleuropneumoniae, an important porcine respiratory pathogen, and the identification of AMR genes in whole genome sequence (wgs) data. Susceptibility of the isolates to nine antimicrobial agents (ampicillin, enrofloxacin, erythromycin, florfenicol, sulfisoxazole, tetracycline, tilmicosin, trimethoprim, and tylosin) was determined by agar dilution susceptibility test. Ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 31 publications
3
40
0
Order By: Relevance
“…Other elements that can be transposed are antibiotic resistance genes, and integrative conjugative elements, such as the 56‐kb ICE Apl1 , have been found in the genome of A. pleuropneumoniae , conferring resistance to tetracycline . Furthermore, analysis has also found the tetracycline resistance ( tet (B)) gene as part of the Tn7 insertion and in some isolates it is the only resistance gene in the genome . Hence, insertion of resistance genes could be a possible explanation of the variance found in the ERIC‐PCR patterns and/or the failure of the toxin PCRs to give the expected profiles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other elements that can be transposed are antibiotic resistance genes, and integrative conjugative elements, such as the 56‐kb ICE Apl1 , have been found in the genome of A. pleuropneumoniae , conferring resistance to tetracycline . Furthermore, analysis has also found the tetracycline resistance ( tet (B)) gene as part of the Tn7 insertion and in some isolates it is the only resistance gene in the genome . Hence, insertion of resistance genes could be a possible explanation of the variance found in the ERIC‐PCR patterns and/or the failure of the toxin PCRs to give the expected profiles.…”
Section: Discussionmentioning
confidence: 99%
“…24 Furthermore, analysis has also found the tetracycline resistance (tet(B)) gene as part of the Tn7 insertion and in some isolates it is the only resistance gene in the genome. 25 Hence, insertion of resistance genes could be a possible explanation of the variance found in the ERIC-PCR patterns and/or the failure of the toxin PCRs to give the expected profiles.…”
Section: Discussionmentioning
confidence: 99%
“…In a Spanish retrospective study from 1994 to 2009, a high or an increasing trend for resistance against beta‐lactam antibiotics, tetracyclines and tilmicosin was recorded, while most isolates were susceptible to amphenicols, fluoroquinolones and ceftiofur (Vanni et al., ). In a recent study, only 33% of UK App isolates were negative for resistance genes, while 57% of the isolates were resistant (as adjudged by MICs) to tetracycline, 48% to sulfisoxazole, 20% to ampicillin, 17% to trimethoprim and 6% to enrofloxacin (Bossé, Li, Rogers, et al., ).…”
Section: Prevention Control and Treatmentmentioning
confidence: 99%
“…Recently, plasmids conferring resistance to florfenicol and chloramphenicol were isolated from App clinical isolates from Greece and Brazil (Bossé et al., ; Cunha da Silva et al., ), and enrofloxacin‐resistant strains have been reported in Taiwan and the UK (Bossé, Li, Rogers, et al., ; Wang et al., ). It has been demonstrated that whole‐genome sequencing can be used as predictor for App resistance to antimicrobial substances (Bossé, Li, Rogers, et al., ). In general, variation in levels of antimicrobial resistance of App isolates within the same herd can be high (Dayao et al., ), and there is not always an association between in vitro test results and success after treatment of disease.…”
Section: Prevention Control and Treatmentmentioning
confidence: 99%
“…Typically, the determination of antimicrobial susceptibility is done either by disk diffusion or minimum inhibitory concentration (MIC) assays. Identification of resistance-specific markers by PCR or microarray hybridization not only corroborates phenotypic results but is also useful for epidemiological purposes, as there are often multiple different genes that can confer resistance to a given antimicrobial agent (Bossé et al, 2017). With the increasing throughput and decreasing cost of DNA sequencing, whole genome sequencing (WGS) may be an alternative for routine surveillance of resistance profiles and for identification of emerging resistances (Mahé and Tournoud, 2018).…”
Section: Introductionmentioning
confidence: 99%